2011
DOI: 10.1007/s10735-011-9334-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyperbaric oxygen treatment on aspiration pneumonia

Abstract: We have studied whether hyperbaric oxygen (HBO) prevents different pulmonary aspiration materials-induced lung injury in rats. The experiments were designed in 60 Sprague-Dawley rats, ranging in weight from 250 to 300 g, randomly allotted into one of six groups (n = 10): saline control, Biosorb Energy Plus (BIO), hydrochloric acid (HCl), saline + HBO treated, BIO + HBO treated, and HCl + HBO treated. Saline, BIO, HCl were injected into the lungs in a volume of 2 ml/kg. A total of seven HBO sessions were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…In the same study, activities of antioxidant enzymes SOD and GSH-Px were reduced in the untreated groups and increased in the treated groups. 39 Similarly, our study showed an increase in the MDA levels, but no significant change in the PC levels was observed, in the group where aspiration pneumonitis was created by BAs. In the same group, there was a significant decrease in CAT activity but no change in SOD activities, which is contrary to the results of Sahin et al From these results, we can say that ROS resulted from the damage caused by BAs oxidizing lipids rather than the proteins in the medium, leading to a reduced antioxidant capacity of the medium.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In the same study, activities of antioxidant enzymes SOD and GSH-Px were reduced in the untreated groups and increased in the treated groups. 39 Similarly, our study showed an increase in the MDA levels, but no significant change in the PC levels was observed, in the group where aspiration pneumonitis was created by BAs. In the same group, there was a significant decrease in CAT activity but no change in SOD activities, which is contrary to the results of Sahin et al From these results, we can say that ROS resulted from the damage caused by BAs oxidizing lipids rather than the proteins in the medium, leading to a reduced antioxidant capacity of the medium.…”
Section: Discussionsupporting
confidence: 60%
“…In the literature, a large number of studies examine aspiration pneumonitis caused by stomach acid and food particles. [37][38][39] However, the damage caused by the Figure 1. Histopathologic results of the study groups to which saline, saline þ AT, BA, and BA þ AT were administered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute lung injury is characterized by severe inflammatory response leading to deterioration of gas exchange and till now there is no effective therapy for ALI. The main model to induce acute lung injury in animals is the administration of hydrochloric acid by intra-tracheal route according to Sahin et al. (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Acute lung injury is characterized by severe inflammatory response leading to deterioration of gas exchange and till now there is no effective therapy for ALI. The main model to induce acute lung injury in animals is the administration of hydrochloric acid by intra-tracheal route according to Sahin et al (2011). In our study, the lung injury was induced by applying the HCl model followed by administration of mesenchymal stem cells and compared their activities to the standard drugs for ALI treatment.…”
Section: Discussionmentioning
confidence: 99%